The Tax Impact Analysis in The Telecommunications Industry among Southern African Countries - Mpofu, Queen; Swart, Odette; Masunda, Tariro (Ilomata International Journal of Tax and Accounting, 2025)
Developing countries apply numerous sector-specific taxes to telecommunications. This paper explores the tax burden and implication of multiple taxes on the telecommunications industry’s performance among South African countries. Through a comprehensive examination of the multiple taxes imposed among the countries under study, this study sought to provide an insightful discussion of the impact of multiple taxes on the performance and economic growth of telecoms companies. The aim of the paper is not only to provide a balance assessment and comparisons of tax policies but also to recommend possible ways for regulatory authorities and telecoms services to reap maximum benefits from taxes imposed, including how the different stakeholder groups can navigate the associated challenges effectively. The taxes vary from country to country, and they include Service Excises, Customs and Import Duties, Regulatory Fees, Value-Added Tax and Corporate Income Taxes surcharges. On the downside, challenges of multiple taxes include increased costs, reduced investments, slower expansion and consumer impact. To minimise on the challenges of multiple taxes, this study recommends tax incentives and regulatory stability.